APPLICATION OF SNOWBALL THROWING LEARNING MODEL TO IMPROVE PKN LEARNING OUTCOMES ON THE MATERIAL OF RIGHTS AND OBLIGATIONS AS CITIZENS OF GRADE V STUDENTS AT SD N 24 LUBUKLINGGAU - Rindu Tiara Gina (Teaching and General Education Studies, 2025)
This study aims to improve student learning outcomes in Citizenship Education (PKN) through the application of the Snowball Throwing learning model. The focus of the material taught is on the rights and obligations of citizens. The background of this study is the low learning outcomes of students in the subject of civics caused by the lack of student activity and involvement in the conventional learning process. We conducted this study in class V of SD Negeri 24 Lubuklinggau, using a sample of 22 students. The research method used was a quasi-experimental approach with a one-group pretest-posttest design. Data collection techniques were carried out through multiple-choice tests of 17 valid questions given before and after the application of the learning model. The results showed that the average pre-test score of students was 45.98 and increased to 83.13 during the post-test. The percentage of student learning completion reached 90%, which indicates that most students have achieved the Minimum Completion Criteria (KKM). Hypothesis testing using the z-test produced a Zcount value of 7.76 and a Ztable of 1.64 at a significance level of 0.05, so it can be concluded that student learning outcomes after the application of the *Snowball Throwing* model experienced a significant increase. Thus, the *Snowball Throwing* learning model has proven effective in improving students' PKN learning outcomes, especially in the material on rights and obligations as citizens. This model is also able to increase student activity, critical thinking skills, and the ability to work together in groups. This model is recommended for broader use in elementary civics classes to foster active learning and improve student participation. Future research may compare its effectiveness with other cooperative learning strategies.